Overcoming the Challenges Imposed by Humoral Immunity to AAV Vectors to Achieve Safe and Efficient Gene Transfer in Seropositive Patients - Gross, David-Alexandre; Tedesco, Novella; Leborgne, Christian; Ronzitti, Giuseppe (Frontiers in Immunology, 2022)
One of the major goals of in vivo gene transfer is to achieve the long-term expression of therapeutic transgenes in terminally differentiated cells. The extensive clinical experience and the recent approval of Luxturna® (Spark Therapeutics, now Roche) and Zolgensma® (AveXis, now Novartis) place vectors derived from adeno-associated viruses (AAV) among the best options for gene transfer in multiple tissues. Despite these successes, limitations remain to the application of this therapeutic modality in a wider population. AAV vectors were originally selected because, despite infecting humans, they were not associated with any evident disease. This initial advantage is now revealing as a limitation because part of the human population, exposed to wild-type AAV, develop anti-AAV antibodies able to neutralize the vectors derived from the virus. Injection of AAV in humans is generally well-tolerated although the immune system can activate after the recognition of AAV vectors capsid and genome. The formation of high-titer neutralizing antibodies to AAV after the first injection precludes vector re-administration. Thus, both pre-existing and post-treatment humoral responses to AAV vectors greatly limit a wider application of this gene transfer modality. Different methods were suggested to overcome this limitation. The extensive preclinical data available and the large clinical experience with the control of AAV vectors immunogenicity are key to clinical translation and to demonstrate the safety and efficacy of these methods and ultimately bring a curative treatment to patients.